The Relationship between Physical Fitness and Selected Anthro-pometric and Cardiometabolic Parameters in Adults - Jana Lipkova; Helena Medekova; Lukas Chovanec; Katarina Hirosova; Martin Samohyl; Ivana Kachutova; Lubica Argalasova; Jana Jurkovicova (Tehran University of Medical Sciences, 2021)
No Abstract